2023
DOI: 10.3390/molecules28041769
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Insight into the Ullmann Homocoupling Reactions Performed in Heterogeneous Catalytic Systems

Abstract: The Ullmann reaction has been reported to be the first cross-coupling reaction performed by using a transition metal catalyst. This reaction has been initially considered as the copper-catalyzed homocoupling of aryl halides, leading to the formation of symmetrical biaryl compounds via the generation of novel C–C bonds. Although this reaction has been extensively studied in recent decades and valuable results have been achieved, there are still considerable efforts focused on the development of novel catalytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 88 publications
0
0
0
Order By: Relevance
“…Whereas recent studies on the Ullmann homocoupling reactions clearly indicated the predominance of heterogeneous Pd catalysts [15], C-N heterocoupling reactions have still been preferably conducted by using more readily available and less toxic Cu-based catalysts [16][17][18][19][20][21]. The subject of the current review is the presentation of the recent progress achieved in the Ullmann-type N-arylation reactions performed in heterogeneous systems, including the utilization of Cu and Pd-based catalysts and magnetic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas recent studies on the Ullmann homocoupling reactions clearly indicated the predominance of heterogeneous Pd catalysts [15], C-N heterocoupling reactions have still been preferably conducted by using more readily available and less toxic Cu-based catalysts [16][17][18][19][20][21]. The subject of the current review is the presentation of the recent progress achieved in the Ullmann-type N-arylation reactions performed in heterogeneous systems, including the utilization of Cu and Pd-based catalysts and magnetic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Novel synthesis procedures based on bilization of catalytically active metal species or organometallic complexes on v port materials provided reusable heterogeneous catalysts with improved pe [14]. Whereas recent studies on the Ullmann homocoupling reactions clearly in predominance of heterogeneous Pd catalysts [15], C-N heterocoupling reaction been preferably conducted by using more readily available and less toxic Culysts [16][17][18][19][20][21]. The subject of the current review is the presentation of the rece achieved in the Ullmann-type N-arylation reactions performed in heterogeneo including the utilization of Cu and Pd-based catalysts and magnetic nanopart…”
Section: Introductionmentioning
confidence: 99%